2012
DOI: 10.1007/s00784-012-0692-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of zirconia sintering temperature on flexural strength, grain size, and contrast ratio

Abstract: OBJECTIVE: This study investigated the effect of sintering temperatures on flexural strength, contrast ratio, and grain size of zirconia. MATERIALS AND METHODS: Zirconia specimens (Ceramill ZI, Amann Girrbach) were prepared in partially sintered state. Subsequently, the specimens were randomly divided into nine groups and sintered with different final sintering temperatures: 1,300°C, 1,350°C, 1,400°C, 1,450°C, 1,500°C, 1,550°C, 1,600°C, 1,650°C, or 1,700°C with 120 min holding time. Three-point flexural streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
255
3
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 293 publications
(297 citation statements)
references
References 38 publications
23
255
3
16
Order By: Relevance
“…Previous studies observed an impact of sintering parameters of zirconia materials on contrast ratio values and reported that higher sintering temperatures/times led to decreased contrast ratio values (Stawarczyk et al, 2013a;Stawarczyk et al 2015). This observation cannot be confirmed by the results of the present study.…”
Section: Two-body Wearcontrasting
confidence: 94%
See 4 more Smart Citations
“…Previous studies observed an impact of sintering parameters of zirconia materials on contrast ratio values and reported that higher sintering temperatures/times led to decreased contrast ratio values (Stawarczyk et al, 2013a;Stawarczyk et al 2015). This observation cannot be confirmed by the results of the present study.…”
Section: Two-body Wearcontrasting
confidence: 94%
“…Conforming to the present study, prior investigations showed that a higher flexural strength of ceramic materials resulted in a higher contrast ratio (Stawarczyk et al, 2013a;Baldissara et al 2010). In this study, the measured flexural strength values for the monolithic zirconia materials ranged between 611 -784 MPa, depending on material type and aging regime.…”
Section: Two-body Wearsupporting
confidence: 71%
See 3 more Smart Citations